Ministry of Trade and Industry Decree No. 497 of the Year 2018 Amending Certain Provisions of Ministerial Decree No. 186 of the year 1978 Promulgating the Executive Regulations of Law No. 24 of the Year 1977 Concerning the Industrial Register = وزارة التجارة والصناعة قرار رقم 497 لسنة 2018 بتعديل بعض أحكام القرار الوزراى رقم 186 لسنة 1978 باللائحة التنفيذية للقانون رقم 24 لسنة 1977 فى شأن السجل الصناعى - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic